Studies on the alkaloid production of genetically transformed and non-transformed cultures of Lobelia inflata L. - Szőke, E.; Bálványos, I.; Kursinszki, L.; Krajewska, A.; Mészáros, A.; Neszmélyi, A. (International Journal of Horticultural Science, 2001)
The investigations of the growth and alkaloid production of cell suspension-, callus-, organized- and hairy root cultures from Lobelia inflata L. proved that these cultures are able to synthesize the characteristic piperidine alkaloids of the intact plant. Alkaloid precursor amino acids (Phe, Lys) and plant growth regulators affect not only the growth and differentiation of tissue cultures but also their secondary metabolism. The synthetic regulator Sz/I I combined with Phe increased the total alkaloid content considerably in callus- and organized cultures; regulator Sz/28 especially increased the lobeline content (in organized cultures in response to Lys, in callus tissues as a result of Phe application). With the aim of optimizing growth and alkaloid production of the genetically transformed hairy root cultures of Lobelia inflata L. we studied the effect of some growth regulators (NAA, IAA, kinetin) and precursor amino acids (Lys, Phe). The kinetin had inhibiting effect on the growth and lobeline production of the hairy roots. The IAA and NAA increased the biomass formation and lobeline production. The highest lobeline level was detected in tissues cultivated on hormone-free medium containing Phe.